Tianeptine is associated with lower risk of suicidal ideation worsening during the first weeks of treatment onset compared with other antidepressants: A naturalistic study. (January 2018) - Nobile, B.; Jaussent, I.; Gorwood, Ph.; Lopez Castroman, J.; Olié, E.; Guillaume, S.; Courtet, Ph.
Abstract: Worsening of suicidal ideation during the first weeks of antidepressant treatment is a poorly understood phenomenon that prompted regulatory bodies to issue specific warnings. To better understand the causes of this phenomenon, this study compared the risk of suicidal ideation worsening in patients taking different types of antidepressant medications. To this aim, 4017 depressed adult outpatients were followed by general practitioners and psychiatrists throughout France for 6 weeks after prescription of an antidepressant treatment. The main study outcomes were to monitor changes (worsening or improvement) in suicidal ideation between baseline (treatment onset) and the study end (week 6) and to determine the remission rates according to the treatment type. Depression severity was assessed with the patient-administered Hospital Anxiety and Depression Scale and suicidal ideation with the 9-item Montgomery-Asberg Depression Rating Scale and the Hopelessness Scale. Use of tianeptine, a mu-opioid receptor agonist was significantly associated with a lower risk of suicidal ideation worsening compared with other antidepressants in the first 6 weeks of treatment. Conversely, remission rates were not significantly affected by the treatment type. Our results highlight a potential interest of opioid agonists to reduce the risk of worsening of suicidal ideation at antidepressant initiation.